2021
DOI: 10.3389/fimmu.2021.708678
|View full text |Cite
|
Sign up to set email alerts
|

ILC1s and ILC3s Exhibit Inflammatory Phenotype in Periodontal Ligament of Periodontitis Patients

Abstract: Innate lymphoid cells (ILCs) are emerging as important players in inflammatory diseases. The oral mucosal barrier harbors all ILC subsets, but how these cells regulate the immune responses in periodontal ligament tissue during periodontitis remains undefined. Here, we show that total ILCs are markedly increased in periodontal ligament of periodontitis patients compared with healthy controls. Among them, ILC1s and ILC3s, particularly NKp44+ILC3 subset, are the predominant subsets accumulated in the periodontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Both protective and deleterious roles of ILCs in diabetes have been emerging (Miani et al, 2018). Recently, it was reported that ILC3s are the predominant subset in the periodontal tissue of periodontitis in comparison with the healthy people (Li et al, 2021). And our data showed that periodontitis microbiota helped the ILC3s to overexpress in the small intestine and spleen and the intestinal IL22 from ILCs, which might be critical to promote inflammatory immune regulation in the progression of T1D.…”
Section: Discussionmentioning
confidence: 63%
“…Both protective and deleterious roles of ILCs in diabetes have been emerging (Miani et al, 2018). Recently, it was reported that ILC3s are the predominant subset in the periodontal tissue of periodontitis in comparison with the healthy people (Li et al, 2021). And our data showed that periodontitis microbiota helped the ILC3s to overexpress in the small intestine and spleen and the intestinal IL22 from ILCs, which might be critical to promote inflammatory immune regulation in the progression of T1D.…”
Section: Discussionmentioning
confidence: 63%
“…ILC3s are regulated by cytokines, which are produced by mononuclear phagocytes or triggered by intestinal microbiota [ 27 ]. ILC3s are also the predominant subset in the periodontal tissue of periodontitis, and they were activated by producing more IL-17A and IFN-γ in comparison with the healthy ones [ 28 ]. In our study, ILC3s were increased by F. nucleatum , thus we speculated that ILC3s might participate in the progression of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…ILC1s are a heterogeneous mixed-cell population, a class of helper ILC1 (also known as tissue-resident ILC1), characterized as lin − CD127 + CD117 − CRTH2 − NKp44 − , with the ability to express T-bet and produce TNF-α and IFN-γ. It has been determined that human gingival tissue is dominated by the ILC1 subgroup [ 65 ], with the largest number of ILC1s in the periodontium and gingiva (approximately 50% of total ILC1s) [ 66 ]. In addition, a small subset of RANKL-expressing ILC1s was also found, which may play an immune regulatory role in gingivitis and periodontitis lesions [ 65 ].…”
Section: Ilcs In Periodontal Homeostasismentioning
confidence: 99%